Diyabetik ayakkabıların, diyabetik periferik nöropatili hastalarda denge ve fiziksel aktiviteye etkisi - Arısoy, Merve (İstanbul Medipol Üniversitesi, Sağlık Bilimleri Enstitüsü, 2022)
Bu çalışma diyabet ve nöropatili kişilerde kullanılan diyabetik ayakkabıların denge ve fiziksel aktivite üzerindeki etkisini araştırmak için tasarlandı. Çalışmaya yaşları 45-85 yaş arasında değişen, toplam 20 birey dahil edildi. Bireyler yalın ayak, gündelik (casual) ayakkabı, soft ayakkabı, diyabetik ayakkabılı olarak statik denge, dinamik denge ve fiziksel aktivite açısından değerlendirildi. Çalışmadan elde edilen sonuçlara bakıldığında; diyabetik periferik nöropati bireylerde ayakkabı kullanımının denge ve fiziksel aktivite yönünden daha iyi sonuç elde edilmiştir (p<0,05). Tüm bireylerde diyabetik ayakkabı,ayakkabısız ve diğer ayakkabılara göre denge ve fiziksel aktivitete daha iyi sonuçlar verdi (p<0,05). Diyabetik nöropatili bireyler için kullanılan soft ayakkabının ise dengeyi bozduğu gözlemlenmiştir (p>0,05).Fiziksel aktivite değerlendirilmesinde yalın ayak koşuluna göre ayakkabı kullanımının aktivite düzeyini olumlu etkilediği gözlenmiştir(p<0,05).Sonuç olarak, diyabetik periferik nöropatili hastalarda önerilene soft ayakkabılar yerine diyabete özel ayakkabıların kullanılmasının denge ve fiziksel aktivite yönünden daha yararlı olacağına,soft ve diğer gündelik ayakkabıların ise olumsuz sonuçlar doğurduğu bu çalışmamız göstermiştir.

This study was designed to investigate the effect of diabetic shoes used on balance and physical activity in people with diabetes and neuropathy. A total of 20 individuals aged between 45-85 years were included in the study. Individuals were evaluated in terms of static balance, dynamic balance, and physical activity with bare feet, casual shoes, soft shoes, and diabetic shoes. Considering the results obtained from the study; It was observed that shoe use was an important factor in favor of individuals in terms of balance and physical activity in individuals with diabetic peripheral neuropathy (p<0.05). When the balance and physical activity tests performed without shoes and other shoe conditions were compared in all individuals, it was determined that diabetic shoes affected balance and physical activity (p<0.05). In terms of balance, it was observed that diabetic shoes affected the balance positively (p<0.05), but the use of soft shoes negatively affected the balance (p>0.05). In the evaluation of physical activity, it was observed that the use of shoes had a positive effect on the activity level (p<0.05). As a result, it has been determined that there is a need for more studies including the effects of diabetic shoes on individuals with diabetic peripheral neuropathy characteristics, and the evaluation of the effect of long-term use of these shoes on balance and physical activity.
Effect of diabetic shoes on balance and physical activity in patients with diabetic peripheral neuropathy
Keywords: Ayakkabı; Denge; Fiziksel Aktivite; Periferik Nöropati; Tip 2 Diyabetes Mellitus; Balance; Footwear; Peripheral Neuropathy; Physical Activity; Type 2 Diyabetes Mellitus